ANOMALI HETERODOKSA DALAM PRAKTIK KOMUNIKASI KELOMPOK MANTONGAN PADA PRODUKSI GARAM RAKYAT DI SURABAYA - Moch Imron Rosyidi; Budi Guntoro; Alia Bihrajihant Raya; Erwin Rasyid (Institut Pertanian Bogor, 2020)
People's salt production in Surabaya mainly relies on mantongan, a name for salt production labor in Madura. Mantongan experiences discrimination and pressure from its landlord and strives to resist the oppression. Pierre Bourdieu believes that the oppressor can practice a doxa to strengthen their position in the social structure. This doxa could only be diminished when a heterodoxa appeared. This study is aimed to analyze how heterodoxa and doxa operate in the habitus between mantongan and the landlord. This study uses qualitative method with a critical approach. The informant of this study are mantongan and landlord in Surabaya. Pierre Bourdieu's Social Practice is used as theory. This study shows that heterodoxa could only be achieved when the social structure dwindles. This finding contradicts Bourdieu's concept of heterodoxa. The group communication of community salt production, showed that mantongan is able to contest and rebel under the pressure of the landlord. The concept of doxa and orthodoxy here is no longer valid when mantongan is in its lowest point. This result is seen as an anomaly in Bourdieu’s thought of social practice.